2021
DOI: 10.1007/s40266-021-00833-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Cumulative Anticholinergic Burden Among Older Long-Stay Nursing Home Residents with Overactive Bladder

Abstract: Background Overactive bladder (OAB), the primary cause of urinary incontinence in nursing homes, is commonly treated with anticholinergic medications; however, the elderly population is vulnerable to the adverse effects associated with anticholinergic burden. Given the relatively high prevalence of OAB among nursing home residents, it is important to understand the magnitude of anticholinergic burden in this population. Objectives The objectives of this study were to (1) examine the prevalence of cumulative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Finally, a population-based study of elderly individuals in Finland revealed that level of anticholinergic burden was associated with a greater risk of hospitalization [23]. Although there is extensive anticholinergic use and associated anticholinergic burden among nursing home residents [25,26], the extent to which anticholinergic burden is associated with healthcare resource use (HCRU) and costs in a nursing home setting is currently unknown.…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, a population-based study of elderly individuals in Finland revealed that level of anticholinergic burden was associated with a greater risk of hospitalization [23]. Although there is extensive anticholinergic use and associated anticholinergic burden among nursing home residents [25,26], the extent to which anticholinergic burden is associated with healthcare resource use (HCRU) and costs in a nursing home setting is currently unknown.…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
“…We recently evaluated anticholinergic burden among long-stay nursing home (LSNH) residents and found that nearly 90% of those with OAB were exposed to varying levels of burden, two-thirds of whom demonstrated moderate-to-high levels. Level of exposure (no, low, moderate, or high) was ascertained by evaluating a drug's anticholinergic activity and patient-specific dosing [25]. Given the anticholinergic burden and impact of this burden on healthcare, it is particularly important to assess the healthcare resource utilization and costs associated with anticholinergic burden among LSNH to understand the resource implications of managing OAB.…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
See 2 more Smart Citations